Characteristics of ST11 KPC‐2‐producing carbapenem‐resistant hypervirulent Klebsiella pneumoniae causing nosocomial infection in a Chinese hospital. Issue 6 (6th May 2022) - Ouyang, Pengwen; Jiang, Bin; Peng, Na; Wang, Juan; Cai, Liang; Wu, Yi; Ye, Jianrong; Chen, Yiping; Yuan, Hao; Tan, Chaochao; Tan, Liming; Xie, Liangyi
Abstract: Background: The purpose of our study is to analyze the microbiological and clinical characteristics of carbapenem‐resistant hypervirulent Klebsiella pneumoniae (CR‐hvKP) that causes nosocomial infection. Methods: We collected the carbapenem‐resistant K . pneumoniae (CRKP) strains that caused nosocomial infection in a hospital in China and collected the relevant clinical data. We characterized these strains for their antimicrobial and virulence‐associated phenotype and genotype and analyzed the clonal relatedness. We screened hypervirulent strains and compared them with non‐hypervirulent strains. Results: We retrospectively analyzed 62 CRKP strains that caused nosocomial infection in a tertiary hospital within 1 year, of which 41 (41/62, 66.1%) CRKP were considered as CR‐hvKP. All CR‐hvKP strains were multi‐drug resistance (MDR) and the vast majority of isolates (39/41, 95.1%) were ST11 KPC‐2‐producing strains. Two hypermucoviscous isolates and 4 capsular types were found in 41 CR‐hvKP. Twenty‐nine isolates (29/41, 70.7%) showed hypervirulence in Galleria mellonella infection model. PFGE showed that ST11‐KL47 CR‐hvKP and ST11‐KL64 CR‐hvKP exhibited a high degree of clonality, while non‐hypervirulent strains were not significant. CR‐hvKP had higher positive rates of bla KPC‐2 and bla CTX‐M‐65 and higher levofloxacin resistance ( p < 0.001, p = 0.005 and p = 0.046, respectively) when compared to the non‐hypervirulent strains. There was no significant difference between the two groups in terms of in‐hospital mortality (7/41, 17.1% vs 5/21, 23.8%, p = 0.743). Conclusion: Our research finds that ST11 KPC‐2‐producing CR‐hvKP is the main type of CRKP that caused nosocomial infection, and clonal spread has occurred. We provide more information about CR‐hvKP in health care. Abstract : Our research finds that ST11 KPC‐2‐producing CR‐hvKP is the main type of CRKP that caused nosocomial infection, which poses a new threat to people's health. And we provide more information about CR‐hvKP in health care.